`Pancasila` is an Awaited Messiah: A Metaphor Study on `Pancasila Mencinta`, a Collection of Poems - Susanto Susanto (Universitas Muhammadiyah Semarang, 2018)
Instead of being a philosophy of nation, Pancasila is part of discourse in which its meaning are still made, remade and negotiated. Through empiric experiences, people try to make sense of the concept of Pancasila and how it manifested in people action to be defined as „Pancasilais’ (bring Pancasila as way of life or ideology). The concept and act of „Pancasilais’ can be traced from the metaphor people made in their works. Pancasila Mencinta is a collection of poems made by seventeen (17) Indonesian poets trying to make sense of Pancasila and being “Pancasilais”. In this paper, the collection of poem above was analyzed from the perspective of metaphor study. The aim of this research was to find concept of Pancasila as ideology in view of poets from the metaphor found in their poems. Lakoff and Johnson theory of conceptual metaphor was used to reveal the poets‟ concept and understanding of Pancasila. The data were collected through library research by collecting supported data from journals, books and other related sources. Data were analyzed by 5 steps offered by Steen (2002); they are metaphorical focus, metaphorical idea, metaphorical comparison, metaphorical analogy, metaphorical mapping. The result of the study showed that Pancasila is understood as holy book which can solve all problem of the nation. Even all problems are caused by people leaving and forgetting Pancasila. This understanding is influence by the experience of religion. Therefore, Pancasila is understood as dogma just like religion.